Low-chromium washing-free anti-oxidation liquid for electrolytic copper foil as well as preparation method and washing-free anti-oxidation process of low-chromium washing-free anti-oxidation liquid

By using a low-chromium, waterless anti-oxidation solution and a stepped hot air drying process, a dense composite film is formed, which solves the problems of weather resistance and environmental protection of electrolytic copper foil, and achieves efficient anti-oxidation protection, making it suitable for electrolytic copper foil used in lithium-ion batteries.

CN121023490APending Publication Date: 2025-11-28SICHUAN MINGFENG ELECTRONIC MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511178961.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-22
Publication Date
2025-11-28

AI Technical Summary

Technical Problem

Existing anti-oxidation treatments for electrolytic copper foil suffer from poor weather resistance, easy failure, and insufficient environmental friendliness. In particular, they are unable to meet the long-term stability requirements of lithium-ion batteries under high temperature and high humidity environments.

Method used

The low-chromium, waterless anti-oxidation solution, which includes components such as chromium sulfate, ammonium molybdate, γ-aminopropyltriethoxysilane, phytic acid, nano-silica, sodium tartrate, and citric acid, is used to form a dense composite film through aging. A stepped hot air drying process is employed to avoid copper foil warping caused by traditional high-temperature drying.

Benefits of technology

It achieves a more environmentally friendly and reliable antioxidant protection while reducing chromium content, with an antioxidant lifespan increased by 12 times and no water washing step required, making it a suitable current collector solution for high energy density power batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005560227150000081
    Figure BDA0005560227150000081
  • Figure BDA0005560227150000091
    Figure BDA0005560227150000091
Patent Text Reader

Abstract

The invention belongs to the technical field of electrolytic copper foil preparation, and discloses a low-chromium washing-free anti-oxidation liquid for an electrolytic copper foil, a preparation method of the low-chromium washing-free anti-oxidation liquid and a washing-free anti-oxidation process. The anti-oxidation liquid comprises the following components: chromium sulfate, ammonium molybdate, gamma-aminopropyltriethoxysilane, phytic acid, nano silicon dioxide, sodium tartrate, citric acid, a pH value regulator and water. According to the invention, the synergistic ratio of chromium sulfate, ammonium molybdate and gamma-aminopropyltriethoxysilane is limited, and nano silicon dioxide is introduced to enhance the compactness of the film layer, so that the chromium content is remarkably reduced, and meanwhile, efficient anti-oxidation protection under a washing-free condition is realized. The matched stepped hot air drying process further avoids the problem of copper foil warping caused by traditional high-temperature drying, and a more environment-friendly and more reliable surface treatment solution is provided for the electrolytic copper foil for the lithium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of electrolytic copper foil preparation, and particularly relates to a low-chromium water-washing-free anti-oxidation solution for electrolytic copper foil, a preparation method thereof and a water-washing-free anti-oxidation process. BACKGROUND

[0002] In the field of lithium ion battery manufacturing, the surface stability of electrolytic copper foil as the core material of the negative electrode current collector directly affects the conductivity and cycle life of the battery. However, copper foil is easily oxidized in the air, forming a copper oxide or cuprous oxide layer, which increases the contact resistance and thus affects the overall efficiency of the battery. The traditional anti-oxidation treatment process generally uses hexavalent chromium passivation solution, which can effectively inhibit the oxidation of copper foil, but hexavalent chromium has strong carcinogenicity and environmental toxicity.

[0003] To meet environmental protection requirements, the industry has gradually shifted to low-toxicity trivalent chromium passivation systems, but the existing technology still has obvious deficiencies. For example, trivalent chromium passivation solution usually requires a subsequent water washing step to remove surface residues, which not only increases wastewater treatment costs, but also may cause secondary pollution of copper foil due to incomplete water washing. In addition, completely chromium-free alternatives (such as molybdate, organosilane, etc.) are more environmentally friendly, but the protective film formed by them has poor weather resistance and is easily damaged, especially in high-temperature and high-humidity environments, making it difficult to meet the requirements of power batteries for long-term stability.

[0004] Therefore, it is of great significance to research a low-chromium water-washing-free anti-oxidation solution for electrolytic copper foil with strong weather resistance, not easy to fail and long-term stability, a preparation method thereof and a water-washing-free anti-oxidation process. SUMMARY

[0005] The purpose of the present application is to provide a low-chromium water-washing-free anti-oxidation solution for electrolytic copper foil, a preparation method thereof and a water-washing-free anti-oxidation process, which solve the problems of poor weather resistance, long-term stability, easy failure and environmental impact existing in the prior art.

[0006] In order to achieve the above-mentioned purpose of the application, the present application provides the following technical solutions:

[0007] The present application provides a low-chromium water-washing-free anti-oxidation solution for electrolytic copper foil, which comprises the following components:

[0008] chromic sulfate, ammonium molybdate, gamma-aminopropyl triethoxysilane, phytic acid, nano silicon dioxide, sodium tartrate, citric acid, a pH value regulator and water.

[0009] Preferably, the anti-oxidation solution comprises the following components in mass fraction:

[0010] Chromium sulfate 0.8-2.5 parts, ammonium molybdate 3-8 parts, gamma-aminopropyl triethoxysilane 4-10 parts, phytic acid 1.5-4.5 parts, nano-silica 0.15-0.75 parts, sodium tartrate 0.7-2.8 parts, citric acid 0.5-1.2 parts and water 65-75 parts.

[0011] Preferably, the pH regulator is ammonia water, and the amount of the pH regulator is such that the pH of the anti-oxidation solution is 3.8-4.2.

[0012] The application also provides a preparation method of the low-chromium anti-oxidation solution for electrolytic copper foil without water washing, which comprises the following steps: mixing chromium sulfate, ammonium molybdate, gamma-aminopropyl triethoxysilane, phytic acid, nano-silica, sodium tartrate, citric acid and water, and then adding a pH regulator and aging to obtain the low-chromium anti-oxidation solution without water washing.

[0013] Preferably, the mixing time is 30-50 min.

[0014] Preferably, the aging time is 20-26 h.

[0015] The application also provides an anti-oxidation process without water washing, which comprises the following steps:

[0016] The copper foil is subjected to anti-oxidation treatment in the anti-oxidation solution, and then taken out and dried to obtain the copper foil after anti-oxidation treatment without water washing.

[0017] The anti-oxidation solution is the anti-oxidation solution described above.

[0018] Preferably, the anti-oxidation treatment is dip coating of the copper foil in the anti-oxidation solution, and the dip coating time is 8-15 s and the dip coating temperature is 45-55 DEG C.

[0019] Preferably, the drying is stepwise hot air drying, which comprises first stage drying, second stage drying and third stage drying.

[0020] In the first stage drying, the temperature is 75-85 DEG C, the time is 2-6 s and the air speed is 8-12 m / s.

[0021] In the second stage drying, the temperature is 115-125 DEG C, the time is 1-3 s and the air speed is 13-17 m / s.

[0022] In the third stage drying, the temperature is 75-85 DEG C, the time is 2-6 s and the air speed is 2-6 m / s.

[0023] According to the above technical solution, compared with the prior art, the application has the following beneficial effects:

[0024] The application realizes high-efficiency antioxidation protection under the condition of free water washing by limiting the synergistic ratio of chromium sulfate, ammonium molybdate and gamma-aminopropyl triethoxysilane and introducing nano-silicon dioxide to enhance the compactness of the film layer, while significantly reducing the chromium content. The matching stepwise hot air drying process further avoids the warping problem of copper foil caused by traditional high-temperature drying, and provides a more environmentally friendly and reliable surface treatment solution for electrolytic copper foil for lithium ion batteries.

[0025] Compared with the prior art, the antioxidation life is increased by 12 times on the basis of reducing the chromium content, and water is not used in the production process, thereby saving the subsequent sewage treatment step, and providing a new generation of current collector solution for high-energy-density power batteries. DETAILED DESCRIPTION

[0026] The application provides a low-chromium water-free anti-oxidation solution for electrolytic copper foil, which comprises the following components:

[0027] chromium sulfate, ammonium molybdate, gamma-aminopropyl triethoxysilane, phytic acid, nano-silicon dioxide, sodium tartrate, citric acid, a pH adjuster and water.

[0028] In the application, the anti-oxidation solution preferably comprises the following components in the following mass fractions:

[0029] The chromium sulfate is preferably 0.8-2.5 parts, further preferably 1-2 parts, and more preferably 1.4-1.8 parts; the ammonium molybdate is preferably 3-8 parts, further preferably 4-7 parts, and more preferably 5-6 parts; the gamma-aminopropyl triethoxysilane is preferably 4-10 parts, further preferably 5-8 parts, and more preferably 6-7 parts; the phytic acid is preferably 1.5-4.5 parts, further preferably 2-4 parts, and more preferably 2.5-3 parts; the nano-silicon dioxide is preferably 0.15-0.75 parts, further preferably 0.3-0.7 parts, and more preferably 0.4-0.6 parts; the sodium tartrate is preferably 0.7-2.8 parts, further preferably 1-2.4 parts, and more preferably 1.5-2 parts; the citric acid is preferably 0.5-1.2 parts, further preferably 0.7-1 part, and more preferably 0.8-0.9 parts; and the water is preferably 65-75 parts, further preferably 67-72 parts, and more preferably 68-70 parts.

[0030] In the application, the pH adjuster is preferably ammonia water, and the amount of the pH adjuster is preferably such that the pH of the anti-oxidation solution is 3.8-4.2, further preferably 3.9-4.1, and more preferably 4.

[0031] In the application, the chromium sulfate as a main passivator is hydrolyzed into Cr(OH)3 colloid under acidic conditions, and forms chemical bonding with the surface of the copper foil; the MoO4 2-The pores of the Cr(OH)3 film layer are filled by adsorption, and the hydrolyzed gamma-aminopropyl triethoxysilane is subjected to polycondensation reaction with the two, forming a composite film with -Si-O-Cr- and -Si-O-Mo- crosslinking structure, which significantly improves the compactness of the film layer.

[0032] In the application, the phosphate groups in phytic acid simultaneously chelate Cr 3+ and Cu 2+ , inhibit the hydrolysis and precipitation of chromium salt; sodium tartrate and citric acid form a binary buffer system, which maintains the stability of the solution through the coordination of carboxyl groups and metal ions, and avoids the agglomeration of nanoparticles.

[0033] In the application, the nano-silicon dioxide is bonded with silane coupling agent through surface silicon hydroxyl groups, forming a physical barrier in the film layer, so that the copper foil has salt spray resistance; when the pH value is adjusted to the weakly acidic range by ammonia water, the solubility and reaction rate of each component reach the best balance, achieving the process goal of no water washing after dip coating.

[0034] The application further provides a preparation method of the low-chromium water-free anti-oxidation solution for electrolytic copper foil.

[0035] In the application, the mixing time is preferably 30-50 min, further preferably 35-45 min, and more preferably 40-42 min.

[0036] In the application, the mixing is preferably first mixing water, sodium tartrate, citric acid, chromium sulfate and ammonium molybdate, then second mixing phytic acid and nano-silicon dioxide, and finally adding gamma-aminopropyl triethoxysilane;

[0037] The first mixing time is preferably 25-35 min, further preferably 26-32 min, and more preferably 28-30 min; the first mixing temperature is preferably 40-50 DEG C, further preferably 42-46 DEG C, and more preferably 44-45 DEG C; and the first mixing stirring rate is preferably 500-800 rpm, further preferably 550-700 rpm, and more preferably 600-650 rpm.

[0038] The second mixing is preferably ultrasonic mixing; the ultrasonic mixing frequency is preferably 38-42 kHz, further preferably 39-41 kHz, and more preferably 40 kHz; and the ultrasonic mixing time is preferably 8-12 min, further preferably 9-11 min, and more preferably 10 min.

[0039] The rate of the addition is preferably 0.6-1 kg / min, further preferably 0.7-0.9 kg / min, and more preferably 0.8 kg / min.

[0040] In the present application, the aging time is preferably 20-26 h, further preferably 21-25 h, and more preferably 22-24 h.

[0041] The present application also provides a water-free washing anti-oxidation process, comprising the following steps:

[0042] The copper foil is subjected to anti-oxidation treatment in the anti-oxidation liquid, and then dried after being taken out, to obtain a copper foil subjected to water-free washing anti-oxidation treatment.

[0043] The anti-oxidation liquid is the anti-oxidation liquid as described above.

[0044] In the present application, the anti-oxidation treatment is preferably dip coating of the copper foil in the anti-oxidation liquid, the dip coating time is preferably 8-15 s, further preferably 10-14 s, and more preferably 12-13 s, and the dip coating temperature is preferably 45-55℃, further preferably 46-52℃, and more preferably 48-50℃.

[0045] In the present application, the drying is preferably stepwise hot air drying, which preferably comprises first stage drying, second stage drying and third stage drying.

[0046] In the first stage drying, the temperature is preferably 75-85℃, further preferably 78-84℃, and more preferably 80-82℃, the time is preferably 2-6 s, further preferably 3-5 s, and more preferably 4 s, and the air speed is preferably 8-12 m / s, further preferably 9-11 m / s, and more preferably 10 m / s.

[0047] In the second stage drying, the temperature is preferably 115-125℃, further preferably 116-124℃, and more preferably 118-120℃, the time is preferably 1-3 s, further preferably 2 s, and the air speed is preferably 13-17 m / s, further preferably 14-16 m / s, and more preferably 15 m / s.

[0048] In the third stage drying, the temperature is preferably 75-85℃, further preferably 76-82℃, and more preferably 78-80℃, the time is preferably 2-6 s, further preferably 3-5 s, and more preferably 4 s, and the air speed is preferably 2-6 m / s, further preferably 3-5 m / s, and more preferably 4 m / s.

[0049] In the present application, the copper foil is preferably subjected to pre-cleaning treatment before being subjected to the oxidation-preventing treatment in the water-free cleaning and oxidation-preventing process, and the pre-cleaning treatment is preferably performed by first performing ultrasonic cleaning and then removing the copper foil from the solution to perform blowing to remove copper powder on the surface of the copper foil.

[0050] The reagent used in the ultrasonic cleaning is preferably anhydrous ethanol, the ultrasonic cleaning time is preferably 3-5 min, further preferably 4 min, the ultrasonic cleaning temperature is preferably 38-42℃, further preferably 39-41℃, and more preferably 40℃; the blowing gas pressure is preferably 0.2-0.4 MPa, further preferably 0.25-0.35 MPa, and more preferably 0.3-0.32 MPa.

[0051] The technical solutions provided by the present application will be described in detail below in conjunction with the examples, but they should not be understood as limiting the scope of protection of the present application.

[0052] The parts in the examples and comparative examples are all parts by mass.

[0053] Example 1

[0054] Preparation of a low-chromium water-free cleaning and oxidation-preventing solution for electrolytic copper foil:

[0055] 70 parts of water, 2.2 parts of sodium tartrate, 1 part of citric acid, 2 parts of chromium sulfate and 5 parts of ammonium molybdate were mixed at 45℃ for 30 min at a rotation speed of 600 rpm, then 3 parts of phytic acid and 0.5 parts of nano silicon dioxide were ultrasonically mixed at a frequency of 40 kHz for 10 min, then 6 parts of γ-aminopropyl triethoxysilane was added to the obtained mixed solution at a rate of 0.8 kg / min to obtain a mixed solution;

[0056] Ammonia water with a concentration of 27 wt% was added to the mixed solution to make the pH value of the obtained solution 4, and then the solution was aged for 24 h to obtain the oxidation-preventing solution.

[0057] Water-free cleaning and oxidation-preventing process:

[0058] The copper foil was placed in anhydrous ethanol and subjected to ultrasonic cleaning at 40 kHz for 4 min at 40℃, then removed from the solution to perform blowing at a gas pressure of 0.3 MPa to remove copper powder on the surface of the copper foil, thereby obtaining the pre-cleaned copper foil;

[0059] Then the pre-cleaned copper foil was placed in the above-mentioned oxidation-preventing solution, immersed and coated at 50℃ for 10 s, then removed, and then sequentially blown with hot air at 80℃ at a wind speed of 10 m / s for 4 s, with hot air at 120℃ at a wind speed of 15 m / s for 2 s, and with hot air at 80℃ at a wind speed of 4 m / s for 5 s, thereby obtaining the water-free cleaning and oxidation-preventing electrolytic copper foil, i.e. completing the water-free cleaning and oxidation-preventing process.

[0060] Example 2

[0061] Preparation of low-chromium water-washing-free anti-oxidation solution for electrolytic copper foil:

[0062] 70 parts of water, 2 parts of sodium tartrate, 0.8 parts of citric acid, 2.2 parts of chromium sulfate and 6 parts of ammonium molybdate were mixed at 45°C at a rotation speed of 600 rpm for 30 min, then 2.5 parts of phytic acid and 0.35 parts of nano-silicon dioxide were ultrasonically mixed at a frequency of 40 kHz for 10 min, then 7 parts of γ-aminopropyl triethoxysilane was added to the obtained mixed solution at a rate of 0.8 kg / min to obtain a mixed solution;

[0063] 27wt% ammonia water was added to the mixed solution to make the pH value of the obtained solution be 4, then the solution was aged for 24 h to obtain an anti-oxidation solution.

[0064] The water-washing-free anti-oxidation process was the same as that in Example 1.

[0065] Example 3

[0066] Preparation of low-chromium water-washing-free anti-oxidation solution for electrolytic copper foil:

[0067] 70 parts of water, 1.4 parts of sodium tartrate, 1 part of citric acid, 1.8 parts of chromium sulfate and 5.5 parts of ammonium molybdate were mixed at 45°C at a rotation speed of 600 rpm for 30 min, then 3.2 parts of phytic acid and 0.45 parts of nano-silicon dioxide were ultrasonically mixed at a frequency of 40 kHz for 10 min, then 5 parts of γ-aminopropyl triethoxysilane was added to the obtained mixed solution at a rate of 0.8 kg / min to obtain a mixed solution;

[0068] 27wt% ammonia water was added to the mixed solution to make the pH value of the obtained solution be 4, then the solution was aged for 24 h to obtain an anti-oxidation solution.

[0069] The water-washing-free anti-oxidation process was the same as that in Example 1.

[0070] Example 4

[0071] Preparation of low-chromium water-washing-free anti-oxidation solution for electrolytic copper foil:

[0072] 70 parts of water, 1.7 parts of sodium tartrate, 1 part of citric acid, 2 parts of chromium sulfate and 4.5 parts of ammonium molybdate were mixed at 45°C at a rotation speed of 600 rpm for 30 min, then 3 parts of phytic acid and 0.4 parts of nano-silicon dioxide were ultrasonically mixed at a frequency of 40 kHz for 10 min, then 5 parts of γ-aminopropyl triethoxysilane was added to the obtained mixed solution at a rate of 0.8 kg / min to obtain a mixed solution;

[0073] 27wt% ammonia water was added to the mixed solution to make the pH value of the obtained solution be 4, then the solution was aged for 24 h to obtain an anti-oxidation solution.

[0074] The water-washing-free anti-oxidation process was the same as that in Example 1.

[0075] Example 5

[0076] Preparation of low-chromium non-water-washing anti-oxidation solution for electrolytic copper foil:

[0077] 70 parts of water, 2 parts of sodium tartrate, 0.8 parts of citric acid, 1.7 parts of chromium sulfate and 4 parts of ammonium molybdate were mixed at 45°C at a rotation speed of 600 rpm for 30 min, then 3.7 parts of phytic acid and 0.6 parts of nano silicon dioxide were ultrasonically mixed at a frequency of 40 kHz for 10 min, then 4 parts of γ-aminopropyl triethoxysilane was added to the obtained mixed solution at a rate of 0.8 kg / min to obtain a mixed solution;

[0078] 27wt% ammonia water was added to the mixed solution to make the pH value of the obtained solution 4, then aged for 24 h to obtain an anti-oxidation solution.

[0079] The non-water-washing anti-oxidation process is the same as Example 1.

[0080] Comparative Example 1

[0081] In Example 1, “5 parts of ammonium molybdate” was changed to “2 parts of ammonium molybdate”, and the other steps were the same as Example 1.

[0082] Comparative Example 2

[0083] In Example 1, “3 parts of phytic acid” was changed to “3 parts of boric acid”, and the other steps were the same as Example 1.

[0084] Comparative Example 3

[0085] In Example 1, “2.2 parts of sodium tartrate” was changed to “3.2 parts of sodium tartrate”, and the other steps were the same as Example 1.

[0086] The electrolytic copper foils obtained in Examples 1-5 and Comparative Examples 1-3 were tested as follows:

[0087] 1. Environmental resistance test:

[0088] (1) Neutral salt spray test: According to the national standard GB / T 10125-2021 “Artificial atmosphere corrosion test-salt spray test”, 5wt% NaCl aqueous solution at 35°C was selected, and the electrolytic copper foil was continuously sprayed, and the appearance of >5% area of oxidation spots was regarded as failure, and the continuous spraying time was calculated, and the test results are shown in Table 1;

[0089] (2) Wet heat cycle test: The electrolytic copper foil was placed in -40°C for 30 min, then placed in an environment with a temperature of 85°C and a humidity of 85% for 30 min as one cycle, and the appearance of >5% area of oxidation spots was regarded as failure, and the cycle number was calculated, and the test results are shown in Table 1.

[0090] Table 1: Environmental resistance test results of the electrolytic copper foils obtained in Examples 1-5 and Comparative Examples 1-3

[0091]

[0092] As shown in Table 1, the neutral salt spray test time of the electrolytic copper foils obtained in Examples 1-5 all exceeded 700 h, the number of hygrothermal cycles all exceeded 100 times, and only slight discoloration appeared on the edges of the copper foils, and no oxidation spots were observed on the surface. In contrast, the electrolytic copper foils obtained in Comparative Examples 1-3 all had dense reddish-brown spots. It can be seen that the low-chromium anti-oxidation solution of the present application realizes long-term stable protection of the copper foils through the synergistic effect of the dense composite film enhanced by nano-silicon dioxide and the optimized components.

[0093] 2. Anti-oxidation performance test:

[0094] The electrolytic copper foils obtained in Examples 1-5 and Comparative Examples 1-3 were baked in an oven at 140°C, and the electrolytic copper foils were observed at 20 min, 60 min and 12 h, respectively. The results are shown in Table 2.

[0095] Table 2: Anti-oxidation performance test results of the electrolytic copper foils obtained in Examples 1-5 and Comparative Examples 1-3

[0096]

[0097] As shown in Table 2, the electrolytic copper foils obtained in Examples 1-5 all had no changes in the 12 h high-temperature oxidation test, proving that the composite film formed by the low-chromium anti-oxidation solution can effectively block the penetration of oxygen, meeting the stringent requirements of power batteries on the long-term stability of copper foils.

[0098] The above only describes the preferred embodiments of the present application, and it should be noted that those of ordinary skill in the art can make several improvements and refinements without departing from the principles of the present application, and these improvements and refinements should also be considered within the scope of protection of the present application.

Claims

1. A low-chromium anhydrous anti-oxidation solution for electrolytic copper foil, characterized in that, The antioxidant liquid comprises the following components: Chromium sulfate, ammonium molybdate, γ-aminopropyltriethoxysilane, phytic acid, nano silica, sodium tartrate, citric acid, pH adjuster, and water.

2. The low-chromium anhydrous anti-oxidation solution for electrolytic copper foil according to claim 1, characterized in that, The antioxidant liquid comprises the following components in parts by weight: Chromium sulfate 0.8–2.5 parts, ammonium molybdate 3–8 parts, γ-aminopropyltriethoxysilane 4–10 parts, phytic acid 1.5–4.5 parts, nano silica 0.15–0.75 parts, sodium tartrate 0.7–2.8 parts, citric acid 0.5–1.2 parts, and water 65–75 parts.

3. The low-chromium anhydrous anti-oxidation solution for electrolytic copper foil according to claim 1 or 2, characterized in that, The pH adjuster is ammonia water, and the amount of pH adjuster used is to make the pH value of the anti-oxidation solution 3.8 to 4.

2.

4. A method for preparing a low-chromium anhydrous anti-oxidation solution for electrolytic copper foil according to any one of claims 1 to 3, characterized in that, The preparation method includes the following steps: mixing chromium sulfate, ammonium molybdate, γ-aminopropyltriethoxysilane, phytic acid, nano silica, sodium tartrate, citric acid and water, then adding a pH adjuster and aging to obtain a low-chromium anhydrous anti-oxidation solution.

5. The method for preparing a low-chromium anhydrous anti-oxidation solution for electrolytic copper foil according to claim 4, characterized in that, The mixing time is 30 to 50 minutes.

6. The method for preparing a low-chromium anhydrous anti-oxidation solution for electrolytic copper foil according to claim 4 or 5, characterized in that, The aging time is 20 to 26 hours.

7. A waterless anti-oxidation process, characterized in that, Includes the following steps: The copper foil is subjected to anti-oxidation treatment in an anti-oxidation solution, and then dried to obtain copper foil with anti-oxidation treatment without water washing. The antioxidant liquid is the antioxidant liquid according to any one of claims 1 to 3.

8. The waterless anti-oxidation process according to claim 7, characterized in that, The anti-oxidation treatment involves immersing the copper foil in an anti-oxidation solution for 8–15 seconds at a temperature of 45–55°C.

9. The waterless anti-oxidation process according to claim 7 or 8, characterized in that, The drying process is a stepped hot air drying process, which includes a first stage drying, a second stage drying, and a third stage drying. During the first stage of drying, the temperature is 75-85℃, the time is 2-6s, and the wind speed is 8-12m / s; In the second stage of drying, the temperature is 115-125℃, the time is 1-3s, and the wind speed is 13-17m / s; In the third stage of drying, the temperature is 75-85℃, the time is 2-6s, and the wind speed is 2-6m / s.